A VIEW OF FERRAJOLI'S GUARANTEE ON THE INFLUENCE OF NEOCONSTITUTIONALISM ON THE PROCESS OF INTERPRETATION AND APPLICATION OF THE LAW IN BRAZIL (ESMAT Magazine, 2024)
This article aims to analyze the misconceptions in the process of interpreting and applying legal norms in Brazil regarding the influence of neoconstitutionalism, which leads the interpreter to ponder the prevalent application of one principle over others revolving around the same cause, bringing morality into law, and along with it, a high level of subjectivity in decision making. Principled constitutionalism, also known as neoconstitutionalism, is said to be responsible for the reconnection between law and morality, developing a new dogmatic of constitutional interpretation where there would be a mandatory distinction between norms and principles, since the latter would be applied through balancing. In contrast to this understanding, Luigi Ferrajoli presents garantist constitutionalism as the precise path to safeguard the essence and values of the constitution, distancing morality from law, bringing as a foundation for the correct application of the law the process of subsumption of the norm, thereby removing the arbitrator’s discretion and re-establishing the normative density of the constitutional text.
Keywords: Neoconstitutionalism. Balancing. Judicial Activism. Guarantism. Subsumption. Legal Certainty.